Pemberdayaan Keluarga dalam Rehabilitasi Medik Paru pada Penderita Penyakit Paru Obstruksi Kronik di Balai Pengobatan Penyakit Paru-Paru Yogyakarta - Ana Adina Patriani, Ira Paramastri, M. Agus Priyanto (Fakultas Kedokteran Universitas Gadjah Mada, 2010)
Background: Chronic Obstructive Pulmonary Disease (COPD) is one of the main causes of morbidity, a leading cause of death and disability in worldwide. In addition COPD imposes a significant burden in terms of disability and impaired quality of life. COPD is projected to increase in much of the world as smoking frequencies rise, the population ages and the contribution in door and out door air pollution. Pulmonary rehabilitation program has been shown in improving quality of life patients with COPD. The success of pulmonary rehabilitation program was influenced by patient’s motivation and support by family members. The family empowerment through training on pulmonary rehabilitation was expected could improve knowledge and skill of the family members of COPD patients and in turn could improve the development of pulmonary function to COPD patients.Objectives: Assess the influence of family empowerment through training on pulmonary rehabilitation in improving the knowledge and skill of family members on pulmonary rehabilitation.Methods: This research was quasi-experimental study by pre and post test with control group design. Subject of the research were 63 family members that was selected randomly. The subject divided into experimental groups (31) and control groups (32). Data collected was conducted by using questionnaires of knowledge and check lists of skill. Data analysis used paired t-test and independent sample t-test with significant level of p=0,05.Results: Level of education, age, knowledge and skill about pulmonary rehabilitation before intervention were not significantly different. After get training on pulmonary rehabilitation, improvement of knowledge and skill in the intervention group was significantly (p<0,05). There was significant difference on knowledge and skill between intervention group with control group. Module has function to resist the family knowledge and skill one month after training.Conclusions: Training pulmonary rehabilitation on family members to COPD patient can improve knowledge and skill about COPD and pulmonary rehabilitation.Keywords: COPD, pulmonary rehabilitation, family empowerment